Giant cell myocarditis with central diabetes insipidus: A case report. Issue 1 (January 2020) - Yamaguchi, Shogo; Sawamura, Akinori; Nakaguro, Masato; Shimoyama, Yoshie; Morimoto, Ryota; Kato, Hiroo; Arao, Yoshihito; Oishi, Hideo; Haga, Tomoaki; Kuwayama, Tasuku; Yokoi, Tsuyoshi; Hiraiwa, Hiroaki; et al.
Abstract: A 51-year-old male, previously diagnosed with central diabetes insipidus due to lymphocytic hypophysitis, presented with fever and dyspnea for 1 week. On arrival, he exhibited hypotension (85/60 mmHg) and sinus tachycardia (110 bpm). His electrocardiogram revealed mild ST elevation on V2–V4. Echocardiography indicated a near-normal (50%) left ventricular ejection fraction (LVEF), although the inferior wall of the left ventricle exhibited severe hypokinesis. Fulminant myocarditis and circulatory insufficiency were suspected, and treatment with dobutamine, 3 μg/kg/min, was started. His LVEF gradually decreased to 20%. On day 17, he developed cardiogenic shock due to ventricular tachycardia and underwent peripheral venous–arterial extracorporeal membrane oxygenation and intra-aortic balloon pumping. Although he did not exhibit polyuria, intravenous vasopressin infusion (0.5 U/h) was performed to maintain normonatremia. Endomyocardial biopsy results revealed the infiltration of scattered giant cells (GCs) and extensive lymphocytes. Despite immunosuppressive therapy (methylprednisolone and cyclosporine), his cardiac function did not recover. On day 36, he received a biventricular assist device; however, he died on day 47 due to the progression of sepsis and multiple organ failure. We speculate that a deficient expression of programmed cell death protein-1 was the cause of both GC myocarditis and lymphocytic hypophysitis. <Learning objective : We describe a fatal case of fulminant giant cell myocarditis complicated by central diabetes insipidus due to lymphocytic hypophysitis. Normonatremia was maintained with intravenous vasopressin 0.5 U/h, and circulatory status was maintained with mechanical circulatory support. We speculate that T-cell programmed cell death protein 1 dysregulation was the common cause of the two disorders.>